Análise das principais cadeias de produção agropecuárias no processo de crescimento econômico do Oeste do Paraná: 1985 2010 - Madureira, Eduardo Miguel Prata (2012)
The western region of Paraná, the subject of this study, is an important region of Paraná State that makes a significant contribution to the primary, secondary and tertiary sectors of the economy. It is an area of over 22,000 km², which corresponds to almost 12% of the total area of the state. It s most important demographic occupation occured when a military colony was set up in Foz do Iguaçu in the early twentieth century, and this intensified with the Vargas government s Westward March policy, which aimed at occupying the entire western side of the country. The farmers who settled in this region came primarily from the states of Rio Grande do Sul and Santa Catarina and they adopted a mixed farming livelihood. The production of pigs, poultry, milk and corn were most popular, and in the late 1960 s the cultivation of soybeans was introduced. The supply chains that were set up in the region helped in the processes of economic and population growth. Thus, this study aims to identify and pinpoint the main productive chains that influenced the region's economic growth between 1985 and 2010, seeking to understand their role in this process. The following objectives were adopted: to estimate and analyze the process of economic growth in cities in the west of Paraná; to analyze changes in the pattern of growth of these cities, and also to identify the influence of the main agro-industrial chains in the growth of these cities. The theoretical approach that was adopted elaborated on the theories of Adam Smith regarding the division of labor and the specialization of production, François Perroux regarding regional development stimulated by specific industries, Albert Otto Hirschman and his theory of regional development through forward linkage effects and backward linkage effects , and finally, Douglas North and his theory of export base. Using data collected from SEAB (Ministry of Agriculture and Supply) as well as IPARDES (Paraná Institute of Economic and Social Development) it is clear that the top five chains that have stimulated economic growth in the region have been soybeans, corn, pork, chicken and milk. These five chains are described, and the manner in which they relate is demonstrated through a flowchart joining the five chains within the same organism. I conclude that the west of Paraná was strongly influenced in its economic and population growth by these chains with their many ramifications. The export base of the region in the early days of colonization was mate and wood, and it is currently represented by the export crops of soybeans and corn, and a series of products developed in the regional agribusinesses that are exported to other cities, states and countries and contribute towards the economic development of the state.